Peran Digital Marketing dan Digital Fundraising dalam Peningkatan Minat Masyarakat Membayar Zakat, Infak, dan Sedekah di Baznas Kabupaten Sumenep - Maisiyah; Rahman, Muktir (Islamic Economics Study Program, Faculty of Sharia and Islamic Economics, Universitas Annuqayah, 2022)
BAZNAS as zakat manager made a new breakthrough in the zakat program by utilizing digital technology, namely digital marketing and digital fundraising which can be done online. The purpose of this study was to analyze the role of digital marketing and digital fundraising in increasing public interest in paying zakat at BAZNAS Sumenep Regency. This research approach uses a qualitative approach, which aims to describe in detail certain phenomena and then analyze them so as to produce descriptive data in the form of written or spoken words from the people or observed behavior. Sources of data used are primary data and secondary data. Data collection techniques are through observation, interviews, and documentation. The data analysis technique used descriptive qualitative analysis. The result of this study is that the digitization of zakat acts as a digital collection and zakat method that makes it easier for BAZNAS Sumenep and Muzakki to save time and costs. In addition, digitalization can facilitate the collection of zakat funds to be more transparent, effective, and efficient. For the implementation of digitization at BAZNAS Sumenep, namely through bank transfers, websites, QR code scans, and social media (Facebook, WhatsApp, and Instagram). The benefits of the Sumenep BAZNAS digitization system are still not felt by the public. This is due to the lack of socialization and promotion carried out by BAZNAS Sumenep to the public regarding the digital system, in addition to the public not having the desire or interest to pay zakat digitally.